Pick Your Poison : The Exchange Rate Regime and Capital Account Volatility in Emerging Markets - Iwata, Shigeru; Tanner, Evan. (Washington, D.C. : International Monetary Fund, 2003)
We characterize a country's exchange rate regime by how its central bank channels a capital account shock across three variables: exchange depreciation, interest rates, and international reserve flows. Structural vector autoregression estimates for Brazil, Mexico, and Turkey reveal such responses, both contemporaneously and over time. Capital account shocks are further shown to affect output growth and inflation. The nature and magnitude of these effects may depend on the exchange rate regime.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet